Effect of concussion on salary and employment: a population-based event time study using a quasi-experimental design - Fallesen, Peter; Campos, Benito (BMJ open, 2020)
Objective Concussions are the most frequent traumatic brain injuries. Yet, the socioeconomic impact of concussions remains unclear. Socioeconomic effects of concussions on working-age adults were studied on a population scale. - Design This population-based, event time study uses administrative data as well as hospital and emergency room records for the population of Denmark. - Setting We study all Danish patients, aged 20-59 years, who were treated at a public hospital or at an emergency room between 2003 and 2017 after suffering a concussion without other intracranial or extracranial injuries (n=55 424 unique individuals). None of the patients had a prior diagnosis of intracranial or extracranial injuries within the past 10 years leading up to the incident. - Primary and secondary outcome measures As primary endpoint, we investigate the mean effect of concussion on annual salaried income within a 5-year period after trauma. In an exploratory analysis, we study whether the potential impact of concussion on annual salaried income is driven by patient age, education or economic cycle. - Results Concussion was associated with an average change in annual salary income of −€1223 (95% CI: −€1540 to −905, p<0.001) corresponding to a salary change of −4.2% (95% CI: −5.2% to −3.1 %). People between 30 and 39 years and those without high school degrees suffered the largest salary decreases. Affected individuals leaving the workforce drove the main part of the decrease. Absolute annual effect sizes were countercyclical to the unemployment rate. - Conclusions Concussions have a large and long-lasting impact on salary and employment of working-age adults on a nationwide scale.